Cumhuriyet Halk Partisi Hükümetlerinin Propaganda Aracı Olarak Öğrenci Faaliyetleri (1945-1950) - Duman, Melih (FSM Vakıf Üniversitesi, 2018)
Bu çalışma 1945-1950 yılları arasında Cumhuriyet Halk Partisi hükümetlerinin yurt dışında ve yurt içinde gerçekleştirdiği öğrenci faaliyetlerini, propaganda/kamu diplomasisi örneği olarak ele almaktadır. II. Dünya Savaşı ertesinde Sovyet Sosyalist Cumhuriyet Birliği’nden (SSCB) algılanan tehdit üzerine Türkiye’nin, değişen dış politikası doğrultusunda, iki yönde propaganda izlediği görülmüştür. Bunlardan ilki ülke içerisinde izlenen Milli Birlik propagandasıdır. İkincisi ise yurt dışında, Sovyetlere karşı Batılı ülkelerin desteğini almak üzere gerçekleştirilen tanıtıcı propagandadır. Çalışmamız, her iki propaganda çalışmasıyla bağlantılı olan ve aynı zamanda 1945-1950 dönemi için istisnai sayılabilecek kültürel-diplomatik propaganda örneği açısından eğitim ve öğrenci faaliyetlerini değerlendirmektedir.

This study is an evaluation of the propaganda/public diplomacy the Republican People’s Party (CHP) governments carried out between 1945-1950 in terms of student activities both at home and abroad. After feeling threatened by the Union of Soviet Socialist Republics (USSR) following World War II, Turkey pursued two types of propaganda in line with their changing foreign policy. First was the National Unity Propaganda, which Turkey used within its borders. The second was a promotional propaganda, which it carried out abroad in order to gain the support of western countries against the Soviets. Within the framework of this study, educational and student-oriented activities that are connected to both propagation efforts will be evaluated, while at the same time, it will be weighted from the perspective of cultural-diplomatic propaganda, which can be counted as an exceptional example for the 1945-1950 period.
Student Activities as an Propaganda Tool for Republican Peoples Party Governments (1945-1950)
Keywords: Propaganda; CHP; Kamu diplomasisi; Gagavuz Türkleri; Öğrenci; Public diplomacy; Gagauz Turks; Student